Zabawki „mówiące” w rozwoju mowy dziecka do trzeciego roku życia - Król, Agata (Studia Edukacyjne, 2022)
Speech development is a special period in the life of every human being, when we acquire the ability to communicate non-verbally and verbally, e.g. as a result of language immersion. However, the development of speech is impacted by many factors that can be both negative and positive. The article presents the results of the author’s own research, whose aim was to determine the potential threats to the proper speech development of a child up to 3 years of age, resulting from the use of “talking” toys in line with the manufacturers’ recommendations. During the analysis of recordings presented by “talking” toys, special attention was paid to their articulation and linguistic correctness, prosody and the meaning of spoken words. The article includes a description of the various stages of speech acquisition up to the age of three and a review of terminological and legal issues regarding toys.